Geoinformatics for Intelligent Transportation - Ivan, I (Springer, 2015)
The aim of the book is to present and discuss new methods, issues and challenges involved in geoinformatics’ contribution to making transportation more intelligent, efficient and human-friendly. It covers a wide range of topics related to transportation and geoinformatics. The themes are divided into four main sections: Transport modeling, Sensor data and services, Intelligent transport systems, and Transport planning and accessibility.